EDITORIAL (Theoretical and Applied Linguistics@ro, 2025)
It is with great pleasure and satisfaction that we present the first issue of Theoretical and Applied Linguistics@ro, the newly established journal of the Department of Linguistics of the Faculty of Letters at the University of Bucharest, developed in association with the Centre of Theoretical and Applied Linguistics1 and Bucharest University Press.